Buddhism for couples: a calm approach to being in a relationship - Napthali, Sarah (Allen & Unwin, 2014)
Every now and then - not very often - we meet a woman who has mastered the art of being in a couple, who has managed to keep the flame alive long after the honeymoon period and well into the trials of parenting. Sarah Napthali is not one of these women but is happy for readers to learn from her mistakes. With her trademark emphasis on self-compassion, she explains how she has applied Buddhist teachings to patch things up, hold things together and even, on good days, scale the heights of relationship happiness. Written for both men and women, Buddhism for Couples tackles the loaded subjects of housework, anger, sex, conflict and infidelity, before introducing Buddhist strategies that can enrich a relationship. Applying Buddhist teachings can improve our relationship by guiding us to delve more deeply into our psyches. Through mindfulness and ever-growing self-awareness, the teachings help us to become more familiar with the workings of our minds and bodies, more aware of our thoughts and beliefs, so that we can see our behaviours with more clarity. Alongside Buddhist teachings, Sarah explores the latest psychological research on relationships and discovers numerous overlaps. Humorous and informative, Buddhism for Couples provides a fresh approach to living as a couple, persuading us to leave behind stale, habitual ways of relating that don't seem to work